Determination of Groundwater Flow Pattern in the basement complex terrain of Ado-Ekiti, Southwestern Nigeria - A. Akinola Oyedele; Gbenga Olayanju; Taiwo Oyedele; Kehinde Oyedele; Taofeek Ewumi; Funmi Ogunlana (Indonesian Journal of Geography, 2023)
Hydrostatic level sampling, geo-referencing and Geographic Information System were employed to delineate the major groundwater recharge / discharge zones, the groundwater flow direction and the groundwater divides in Ado-Ekiti metropolis with the objective of groundwater resource protection.  Static water level measurements were made from 108 hand – dug wells evenly distributed on a regional basis. The latitudes, longitudes and elevations above mean sea level of the well points were measured using the Global Positioning System. A mean value of 5.84 ± 2.35 m above mean sea level was observed for the depths to the static water level with a mean value of 408.27 ± 46.06 m above mean sea level for the groundwater head. The contour maps obtained enabled the delineation of the major groundwater recharge / discharge zones, the groundwater flow direction and the groundwater divides with the regional tendency of the underground flow approximately lying along the Northwest – Southeast direction and groundwater divides along the South – Eastern/ South – Western axes of the Central portion. Strict environmental ethics must be enforced around the groundwater recharge / discharge zones and flow directions in order to avoid groundwater contamination.